A Framework to Link International Clinical Research to the Promotion of Justice in Global Health. (20th December 2012) - Pratt, Bridget; Loff, Bebe
Abstract How international research might contribute to justice in global health has not been substantively addressed by bioethics. Theories of justice from political philosophy establish obligations for parties from high‐income countries owed to parties from low and middle‐income countries. We have developed a new framework that is based on Jennifer Ruger's health capability paradigm to strengthen the link between international clinical research and justice in global health. The 'research for health justice' framework provides direction on three aspects of international clinical research: the research target, research capacity strengthening, and post‐trial benefits. It identifies the obligations of justice owed by national governments, research funders, research sponsors, and investigators to trial participants and host communities. These obligations vary from those currently articulated in international research ethics guidelines. Ethical requirements of a different kind are needed if international clinical research is to advance global health equity.